Effect of Cynara scolymus and Silybum marianum extracts on bile production in pigs - Martínez, Guadalupe (2018)
Many of the beneficial effects on productive performance observed when vegetable extracts are incorporated as feed additives in intensive farming can be explained by an increase in bile production. An experiment was conducted to study choleretic and cholagogue effect of a Cynara scolymus extract formulation and of silymarin in pigs. Pigs were cannulated with a T-tube catheter in the bile duct. Bile production was continuously measured and re-infused to the duodenum through Oddi’s sphincter at the same production rate. Treatments: Group A (n = 6), commercial feed; Group B (n = 6), C. scolymus extract (300 g/tonne) and Group C (n = 6), silymarin (300 g/tonne). Bile production was recorded hourly for each animal during 24 h. Total bile acids’ concentrations in bile, just before and one hour after meals were evaluated. Average daily bile production for pigs in group B was 66% higher than for pigs in groups A or C (P <.05). When bile acids’ concentrations before and after meals were compared, only pigs from group B exhibited an increase (P =.0023). From this study, it was concluded that neither choleretic nor cholagogue effects are attained with silymarin supplementation. On the contrary, C. scolymus extract increases bile production and secretion in pigs.